ANALYZING ENTREPRENEURIAL MARKETING ON INNOVATIVE PERFORMANCE - Teofilus Teofilus; Sanju Kumar Singh; Timotius FCW Sutrisno; Anthony Kurniawan (MIX: JURNAL ILMIAH MANAJEMEN, 2020)
Resource Based View (RBV) is used to identify problems faced by SMEs. Based on the results of SWOT analysis, it can be seen that SMEs have six problems. These problems include: limited human resources, lack of advanced technology, not having enough knowledge about the target market, not having a good enough SMES management systems, competitor competition, and price from suppliers that fluctuate. The purpose of this study is to determine the effect of Entrepreneurial Marketing on Innovative Performance. This study uses questionnaire as a research instrument for 35 respondents, SMEs who sell snacks in Surabaya city. The results of this study indicated that Entrepreneurial Marketing, consisting of Market Orientation and Entrepreneurial Orientation, has a positive and significant influence on Innovative Performance of SMEs. This shows that the SMES business unit that implements Entrepreneurial Marketing will experience an increase in the performance of the business unit